Literacy histories as opportunities for learning: reflecting, connecting, and learning from Margaret Meek Spencer. (3rd July 2022) - Cremin, Teresa; Hendry, Helen
ABSTRACT: This paper, drawing on Margaret Meek Spencer's work, considers the value of reflecting on literacy histories, whether of children, teachers, authors or academics. Margaret argued that teachers need to be open to literacy as lived, and to look, listen and learn about literacies that develop without direct instruction and stretch beyond "schooled" expectations. She foregrounded the power of story and narrative play for children's literacy development, the importance of the texts themselves and the particular value of author-artists. We revisit these contributions and link to related national and international research studies which develop her work, registering nonetheless that many of her insights are not yet fully reflected in policy, curricula, or classroom practice. We close by reiterating Margaret's invitation to take a mirror to our literacy histories to enable us to reflect, to connect and to understand in order to support young literacy learners more effectively.